2021
DOI: 10.3389/fpsyg.2021.591682
|View full text |Cite
|
Sign up to set email alerts
|

How Can People Express Their Trait Self-Esteem Through Their Faces in 3D Space?

Abstract: BackgroundTrait self-esteem reflects stable self-evaluation, and it affects social interaction patterns. However, whether and how trait self-esteem can be expressed through behaviors are controversial. Considering that facial expressions can effectively convey information related to personal traits, the present study investigated the three-dimensional (3D) facial movements related to self-esteem level and the sex differences therein.MethodsThe sample comprised 238 participants (46.2% males, 53.8% females). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…This study not only supports prior research that showed behavior markers might be used to assess self-esteem and demonstrates that gait patterns can reflect self-esteem rather effectively, but it also represents a considerable advance in comparison to earlier studies ( 14 , 16 ). More significantly, the use of an omnipresent camera enables the implementation of a real-time, population-based prediction of human psychological traits (self-esteem) scores.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This study not only supports prior research that showed behavior markers might be used to assess self-esteem and demonstrates that gait patterns can reflect self-esteem rather effectively, but it also represents a considerable advance in comparison to earlier studies ( 14 , 16 ). More significantly, the use of an omnipresent camera enables the implementation of a real-time, population-based prediction of human psychological traits (self-esteem) scores.…”
Section: Discussionsupporting
confidence: 86%
“…More importantly, using feature selection with a theoretical foundation improves the explanation of the findings. Last but not least, we significantly expanded the sample size, which improved the reliability of the findings ( 16 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While RRS has been widely employed in ruminative research, the limitations of this scale are also significant, especially regarding the presence of psychological selection (Wang et al, 2020 ; Miao et al, 2021 ). Camouflage, falsification, social approval, and other issues (Dunning et al, 2005 ; Schwarz, 2012 ; Wang et al, 2020 , 2021 ) have greatly affected the acceptance and validity of rumination-related psychological testing. Therefore, further advancements are necessary in inducing ruminative conscious activity accurately, measuring the associated brain activity objectively, and exploring the neural biomarkers of rumination to identify ruminators and predict future rumination for precise psychological selection.…”
Section: Introductionmentioning
confidence: 99%